OPTIMIZATION AND PREPARATION OF SOLID LIPID NANOPARTICLE INCORPORATED TRANSDERMAL PATCH OF TIMOLOL MALEATE USING FACTORIAL DESIGN - KUMAR, PARVEEN; SHRIVASTAVA, BIRENDRA; GUPTA, MADAN MOHAN; SHARMA, ANIL KUMAR (International Journal of Applied Pharmaceutics, 2019)
Objective: Transdermal patch of timolol maleate was prepared in order to increase the permeability of the drug topically. Methods: The timolol maleate (TM) loaded solid lipid nanoparticles (SLN) were prepared by the solvent evaporation method. For the optimization process full factorial (three-factor and three-level), hydroxypropyl methylcellulose (HPMC) range from 100 to 300 mg, ethylcellulose 100 to 200 gm and almond oil 3 to 4 ml. The response noted in form of tensile strength and percent drug release. These transdermal patches were evaluated for physical characterization like weight variation, thickness, percentage moisture absorption, percentage moisture loss, water vapor transmission rate, folding endurance, tensile strength, and content uniformity. Results: Solid lipid nanoparticles of TM were optimized and prepared, the data presented that drug release percent ranged from 66.12 to 91.75. 2FI model was observed to fit for response % drug permeation with a p and F value of 0.0271 and 4.50. The tensile strength varies from 0.358 to 0.508. The linear model was observed to fit for the tensile strength response with a p-value and F-value of<0.0001 and 52.41. Conclusion: The controlled release formulation of Timolol Maleate was successfully optimized and prepared, a study conducted to investigate the effect of different polymers and type of permeation time profiles from Timolol Maleate patches.